Irgm1 (LRG-47), a regulator of cell-autonomous immunity, does not localize to mycobacterial or listerial phagosomes in IFN-γ-induced mouse cells() - Springer, Helen M. (2013)
The interferon-inducible protein Irgm1 (LRG-47) belongs to the family of immunity-related GTPases (IRG) which function in cell-autonomous resistance against intracellular pathogens in mice. Irgm1-deficiency is associated with a severe immunodeficiency syndrome. The protein has been variously interpreted as a direct effector molecule on bacterial phagosomes, on other organelles or as an inducer of autophagy. In this study we have re-examined one of these claims, namely that Irgm1 targets mycobacterial and listerial phagosomes. We found no colocalization of endogenous Irgm1 using two different immunofluorescent staining techniques either in fibroblasts or in macrophages. We have demonstrated the predicted existence of two protein isoforms of Irgm1 derived from differential splicing and described immunological reagents for their detection. Both Irgm1 isoforms localize to the Golgi apparatus and weakly to mitochondria, however only the long Irgm1 isoforms can be detected on endolysosomal membranes. Together with the previous observation that the general immunodeficiency phenotype of Irgm1(−/−) mice is reversed in Irgm1/Irgm3-double-deficient mice, our results argue against a direct effector function of Irgm1 at the bacterial phagosome. We discuss these findings in the context of evidence that Irgm1 functions as a negative regulator of other members of the IRG protein family.